Occurrence and distribution patterns of several marine vertebrates in Golfo Dulce, Costa Rica - Bessesen, Brooke L. (Revista de Biología Tropical, 2015)
Within the months of January-February 2010 and July-August 2011, 55 daily sighting surveys were conducted in Golfo Dulce, a tropical fiord-like embayment in the South Pacific region of Costa Rica. The research objective was to collect baseline data on several marine vertebrates that enter or reside in the Gulf and determine spatial distribution during the study periods. Sighting surveys mainly focused on whales, dolphins, sea turtles and sea snakes. A total of 458 recorded sightings, representing at least 30 marine species, were acquired during 423.7 observation hours across all areas of the embayment. These data, along with information garnered from 82 interviews with local fishermen and tour boat guides, confirmed a wide array of marine species utilizing the inlet for the purposes of foraging, mating, resting and socializing. GIS analyses allowed comparisons of spatial distribution and revealed high-density areas for marine fauna within Golfo Dulce.